(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
The present article investigates the semantic peculiarities of speaking verbs in English and Uzbek and examines their functional role in speech and literary discourse. Speaking verbs constitute an important lexical-semantic group expressing communication, emotional states, speaker attitude, and interpersonal relations. The research aims to analyze the semantic classification, stylistic functions, and linguocultural characteristics of speaking verbs in the two languages. Comparative, semantic, contextual, and functional methods are applied in the study. The analysis demonstrates that speaking verbs in English and Uzbek perform not only nominative functions but also emotional-expressive, evaluative, pragmatic, and text-forming functions. The findings reveal both universal and culturespecific semantic features shaped by communicative traditions and national mentality. The article concludes that speaking verbs occupy an important place in discourse organization and literary characterization in both languages.